KONSEP ADMINISTRASI DAN SUPERVISI PENDIDIKAN - Nuraini Nuraini (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The concept of administration is often interpreted as the process of developing cooperative activities among a group of people to achieve predetermined goals. Specifically, it aims to achieve educational goals. Educational administration is a series or set of processes for controlling the cooperative efforts of a group of people to achieve educational goals in a planned and systematic manner within a specific environment, particularly formal educational institutions. Government Regulation No. 19 of 2005 on National Education Standards, Article 57, states that supervision, which includes managerial supervision and academic management supervision, is carried out regularly and continuously by supervisors or inspectors of educational units and heads of educational units. The National Education Standards Act explains that there are two types of supervision: managerial supervision and academic management supervision or academic supervision. The basic concepts of education administration and supervision explain the definitions of administration and supervision, the objectives and benefits of administration and supervision, the process of educational supervision, approaches, techniques, and methods of educational supervision. The fundamental and most important aspects that must be understood by supervisors, whether school supervisors or supervisors within educational institutions, are the school principals.